An Association Between Phonetic Complexity of Infant Vocalizations and Parent Vowel Hyperarticulation - Marklund, Ellen; Marklund, Ulrika; Gustavsson, Lisa (Frontiers in Psychology, 2021)
Extreme or exaggerated articulation of vowels, or vowel hyperarticulation, is a characteristic commonly found in infant-directed speech (IDS). High degrees of vowel hyperarticulation in parent IDS has been tied to better speech sound category development and bigger vocabulary size in infants. In the present study, the relationship between vowel hyperarticulation in Swedish IDS to 12-month-olds and phonetic complexity of infant vocalizations is investigated. Articulatory adaptations towards hyperarticulation is quantified as difference in vowel space area between IDS and adult-directed speech (ADS). Phonetic complexity is estimated using the Word-Complexity Measure for Swedish (WCM-SE). The results show that vowels in IDS was more hyperarticulated than vowels in ADS, and that parents’ articulatory adaptation in terms of hyperarticulation correlates with phonetic complexity of infant vocalizations. This can be explained either by the parents’ articulatory behavior impacting the infants’ vocalization behavior, the infants’ social and communicative cues eliciting hyperarticulation in the parents’ speech, or the two variables being impacted by a third, underlying variable such as general communicative adaptiveness.